Association of short stature with cognitive assessment in primary school children in Kampung Melayu, Jakarta, Indonesia - Hannisa Rizka Setiawati; Rini Sekartini (World Nutrition Journal, 2020)
Background: In Indonesia, an estimated 23.6% of children aged 5-12 years old are short statured, therefore short stature is made one of the health priorities. Children with short stature are associated with low cognitive levels, so that it will have an impact on quality of life.Methods: This research was conducted in a cross-sectional study at SDN 01 Kampung Melayu, Jakarta, Indonesia. Subjects are children with short stature aged 6-12 years old. Data was taken by measuring height according to age with the curve used by the Centers for Disease Control and Prevention - National Center for Health Statistics (CDC-NCHS) and total value from cognitive assessment using the Cognitive Test Battery for Individuals with and without Intellectual Disabilities (CIID) instrument. This research was conducted aiming to assess cognitive in primary school children with short stature.Results: There were 64 children with short stature in SDN 01 Kampung Melayu with CIID test results for Total Score obtained in the range of 5-26, with mean and standard deviations 13.59 ± 4.54. Non Verbal Score was obtained in the range 7-39, with mean and standard deviations 21.94 ± 7.51. Hopkins Verbal Learning Test obtained range 6-31, with mean and standard deviations 19.36 ± 5.90. Verbal Fluency is obtained in the range of 5-26, with mean and standard deviations 13.59 ± 4.54. Compared with previous studies, subjects with short stature have values similar to those of children with normal stature. No significant difference was found between short stature children with underweight nutritional status and short stature children with normal nutritional status, with p=0.369.Conclusion: There were 64 children with short stature and the total score ranging from 5-26, with mean and standard deviations 13.59 ± 4.54